Instant Qualitative Observation for Performance Information And Its Effect On Some Kinematical Variables Javelin Putting and Achievement In Javelin Throwers U18 - Abdu kareem, Karrar; Abdul kareem, sareeh (Journal of Physical Education, 2019)
The research aim at designing a program for kinematical information recall from thrower and coach as well as identifying its effect on motor transition and some throwing position variables. The subjects were (5) throwers from the national center for gifted in athletics season (2019). The researcher concluded the development in shoulder angular speed as well as development in all velocities and throwing angle values. All development resulted from in achievement development in kinematical variables whether in body and javelin.